1999
DOI: 10.1016/s1097-2765(00)80482-7
|View full text |Cite
|
Sign up to set email alerts
|

ROC1, a Homolog of APC11, Represents a Family of Cullin Partners with an Associated Ubiquitin Ligase Activity

Abstract: We have identified two highly conserved RING finger proteins, ROC1 and ROC2, that are homologous to APC11, a subunit of the anaphase-promoting complex. ROC1 and ROC2 commonly interact with all cullins while APC11 specifically interacts with APC2, a cullin-related APC subunit. YeastROC1 encodes an essential gene whose reduced expression resulted in multiple, elongated buds and accumulation of Sic1p and Cln2p. ROC1 and APC11 immunocomplexes can catalyze isopeptide ligations to form polyubiquitin chains in an E1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
459
1
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 428 publications
(481 citation statements)
references
References 19 publications
17
459
1
4
Order By: Relevance
“…In budding yeast, it is known that there is only one member of the ySAG/yROC/yRbx/Hrt family. Targeted disruption of this gene results in cell death that can be fully rescued by ROC1/Rbx1 Ohta et al, 1999) or ySAG (this report) or ROC2, an N-terminal truncated SAG, as reported (Ohta et al, 1999). Since both ROC1/Rbx1/Hrt1 and SAG has ubiquitin ligase activity when complexed with SCF component, it is likely that SAG/ROC/Rbx/Hrt regulates cell cycle through ubiquitin/proteolysis pathway.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…In budding yeast, it is known that there is only one member of the ySAG/yROC/yRbx/Hrt family. Targeted disruption of this gene results in cell death that can be fully rescued by ROC1/Rbx1 Ohta et al, 1999) or ySAG (this report) or ROC2, an N-terminal truncated SAG, as reported (Ohta et al, 1999). Since both ROC1/Rbx1/Hrt1 and SAG has ubiquitin ligase activity when complexed with SCF component, it is likely that SAG/ROC/Rbx/Hrt regulates cell cycle through ubiquitin/proteolysis pathway.…”
Section: Discussionmentioning
confidence: 54%
“…We showed a morphological cell enlargement and a broad distribution of¯uorescence intensities with an increased DNA content in SAG knockout cells (Figure 4). Several recent ®ndings also support this notion: (1) Xenopus Cdc34, an E2 that binds to SAG/ROC/Rbx/Hrt Ohta et al, 1999;Seol et al, 1999;Skowyra et al, 1999;Tan et al, 1999;Tyers and Willems, 1999) promoted degradation of Wee1 (Michael and Newport, 1998), a key G2/M negative regulator (McGowan and Russell, 1993;Parker and Piwnica Worms, 1992); (2) SCF components, Skp1 and Cul1 were localized to the centrosome and regulated the centrosome duplication cycle in mammalian cells (Freed et al, 1999); and (3) Cdc4, an F-box protein in SCF complex was required for the onset of S phase as well as anaphase in Saccharomyces cerevisiae (Goh and Surana, 1999).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations